The implementation of Regional Medium Term Development Plan policy of Cianjur regency - Denny Aditya Dwiwarman (Jurnal Office, 2021)
Planning can be defined as determining the actions that will be carried out in the future with the aim of achieving what is desired. Planning is often arranged to solve a certain problem at a certain time. Planning is a continuous process, covering two aspects, namely the formulation of the plan and its implementation. Development is a process of implementing activities to make a better change as an application of a predetermined planning process. In the Cianjur Regency RPJMD 2011-2016, it is explained that the policy on public works is directed at road and bridge infrastructure programs, irrigation, water resources, building construction and rural infrastructure development. In accordance with the context of the problem to be studied, this research focuses more on road infrastructure based on tourism in South Cianjur which is expected to increase the purchasing power and welfare of the community, especially those in South Cianjur. This research uses qualitative research. A qualitative approach was chosen because it can be used to reveal and understand something behind a phenomenon that is not yet known or a phenomenon that is little known. The results showed that the implementation of the Cianjur Regency RPJMD policy was deemed not implemented properly, it was proven that good road conditions were around 36.35% and the rest was 64.65%.